Song of Freedom: “The United States of Russia” in the Political Imagination of a Russian-American Adventurer - Vinitsky, Ilya (Journal of Russian American Studies, 2020)
This article explores the imaginative constructions and myth-making of Ivan Narodny, an eccentric Russian émigré, who proposed the utopian idea of the "United States of Russia." The study traces Narodny’s elaborate fabrications, including forged documents and interviews, which shaped perceptions of Russian revolutionary politics in early 20th-century American consciousness. By analyzing these mystifications, Vinitsky highlights how Narodny’s fictional narratives reflect broader themes of idealized revolution and political utopia during periods of historical upheaval. The article underscores the interplay between fiction and reality in shaping cultural and political discourses across transnational contexts.